RANCANG BANGUN TEMPAT SAMPAH PINTAR DENGAN AKUISISI DATA DI MADRASAH ALIYAH AL-HUDA 1 JATILUHUR - Fitra, Rizki; Minarto, Minarto; Tamyiz, Uus Muhammad Husni (Universitas 17 Agustus 1945 Jakarta, 2024)
Design of a Smart Bin with Data Acquisition At Madrasah Aliyah Al-Huda 1 Jatiluhur is a system created to handle waste by integrating trash into the system. In general, trash cans must be checked manually by visiting their location, for this reason the authors conducted research with the aim of designing and building a system that functions to be able to detect garbage levels, temperature levels, humidity, light intensity, and rain, designing system modeling using unified modeling language (UML), namely use case diagrams, activity diagrams, sequence diagrams, and class diagrams. Applications are built on two desktop and mobile platforms, for desktop platforms built using visual basic.net, for databases using MySQL, and mobile platforms built using Android Studio, as well as for system testing using black-box testing, as well as for hardware implementation, the author uses Nodemcu ESP8266 and Arduino Uno. By designing a smart waste bin system with data acquisition, it will help handle waste more effectively and efficiently.